CPT-11 Chemotherapy Rescued A Patient with Atypical Sclerosing Epithelioid Fibrosarcoma from Emergent Condition - Pan, Chun-hua; Han, Xi-qun; Li, Jian-sheng (Chinese Journal of Cancer Research; Vol 24, No 3 (September 01, 2012): Chinese Journal of Cancer Research, 2012)
Sclerosing epithelioid fibrosarcoma (SEF) is a rare and poorly defined variant of fibrosarcoma, but generally insensitive to chemotherapy and progresses with poor prognosis. We report the marvelous effect of irinotecan hydrochloride (CPT-11) chemotherapy in rescuing a patient with atypical SEF from emergent condition, who underwent recurrences after several treatment methods. Small dose of CPT-11 was administered to the patient, with which, the size of superficial mass (cervical lymph node) gradually decreased observed by the naked eyes in 5 days. Xray and CT image proved a marked reduction in the size of the tumor. CPT-11 is valuable for the treatment of this aggressive sarcoma. In condition of emergency caused by sarcoma oppression, administering a tolerable small dose of topoisomerase I-inhibiting drug could be a beneficial choice.